Surface engineered iron oxide nanoparticles generated by inert gas condensation for biomedical applications - Hemben, Aver; Chianella, Iva; Leighton, Glenn J. T. (MDPI, 2021)
Despite the lifesaving medical discoveries of the last century, there is still an urgent need to improve the curative rate and reduce mortality in many fatal diseases such as cancer. One of the main requirements is to find new ways to deliver therapeutics/drugs more efficiently and only to affected tissues/organs. An exciting new technology is nanomaterials which are being widely investigated as potential nanocarriers to achieve localized drug delivery that would improve therapy and reduce adverse drug side effects. Among all the nanocarriers, iron oxide nanoparticles (IONPs) are one of the most promising as, thanks to their paramagnetic/superparamagnetic properties, they can be easily modified with chemical and biological functions and can be visualized inside the body by magnetic resonance imaging (MRI), while delivering the targeted therapy. Therefore, iron oxide nanoparticles were produced here with a novel method and their properties for potential applications in both diagnostics and therapeutics were investigated. The novel method involves production of free standing IONPs by inert gas condensation via the Mantis NanoGen Trio physical vapor deposition system. The IONPs were first sputtered and deposited on plasma cleaned, polyethylene glycol (PEG) coated silicon wafers. Surface modification of the cleaned wafer with PEG enabled deposition of free-standing IONPs, as once produced, the soft-landed IONPs were suspended by dissolution of the PEG layer in water. Transmission electron microscopic (TEM) characterization revealed free standing, iron oxide nanoparticles with size < 20 nm within a polymer matrix. The nanoparticles were analyzed also by Atomic Force Microscope (AFM), Dynamic Light Scattering (DLS) and NanoSight Nanoparticle Tacking Analysis (NTA). Therefore, our work confirms that inert gas condensation by the Mantis NanoGen Trio physical vapor deposition sputtering at room temperature can be successfully used as a scalable, reproducible process to prepare free-standing IONPs. The PEG- IONPs produced in this work do not require further purification and thanks to their tunable narrow size distribution have potential to be a powerful tool for biomedical applications.
Keywords: iron oxide nanoparticles; PVD; Mantis NanoGen Trio; drug delivery